Estimation of fluoride concentrations and pH values of commercially available vitamin water in Bangkok, Thailand - Horsophonphong, Sivaporn; Nuchit, Sirada; Hayibueraheng , Nasibah; Natkunanon, Panthira; Tansiri, Praewpan; Puengsurin, Duangchewan; Surarit, Rudee (Mahidol Dental Journal, 2022)
Objective: Over the last few years, the demand for vitamin water has grown. Water is the main source of fluoride intake, and the acidity of consumed water could contribute to tooth surface erosion. Therefore, the aim of this study was to investigate the fluoride concentrations and pH values of commercially available vitamin water in Bangkok, Thailand. Materials and Methods: Sixty vitamin water products that are commercially available in Bangkok, Thailand were purchased from supermarkets and convenience stores. The fluoride and pH of the vitamin water products were determined using a fluoride ion selective electrode and a pH meter with a glass electrode. Due to the sensitivity of the fluoride ion selective electrode, the fluoride concentrations that were less than 0.02 mg/L were considered 0 fluoride. Results: The pH levels of the 60 vitamin water products ranged from 2.78–9.61 with a median and mean (±SD) of 3.61 and 4.11 (±1.49), respectively. Most of the products (85%, n=51/60) had pH values ≤ 5.5, and 15% (n=9/60) had pH value above 5.5. The fluoride concentrations varied among products. The fluoride concentration in vitamin water ranged from 0–3.17 mg/L with a median of 0.046 mg/L and mean (±SD) of 0.243 (±0.628) mg/L. Most of the products (92%, n=55/60) contained undetectable or low fluoride levels. However, 8.3% of the products (n=5/60) had high levels of fluoride ranging from 1.78-3.17 mg/L with a median of 1.98 mg/L and mean (±SD) of 2.242 (±0.570) mg/L. Conclusion: The vitamin water fluoride concentrations and pH values varied among products. Most of the products had pH levels lower than the critical pH value of enamel. The majority of the products contained low fluoride concentrations. However, 8.3% of the products contained high levels of fluoride that could increase the risk of dental fluorosis in young children.